2014
DOI: 10.1186/s13073-014-0075-5
|View full text |Cite
|
Sign up to set email alerts
|

Alteration in basal and depolarization induced transcriptional network in iPSC derived neurons from Timothy syndrome

Abstract: BackgroundCommon genetic variation and rare mutations in genes encoding calcium channel subunits have pleiotropic effects on risk for multiple neuropsychiatric disorders, including autism spectrum disorder (ASD) and schizophrenia. To gain further mechanistic insights by extending previous gene expression data, we constructed co-expression networks in Timothy syndrome (TS), a monogenic condition with high penetrance for ASD, caused by mutations in the L-type calcium channel, Cav1.2.MethodsTo identify patient-sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
44
0
4

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(51 citation statements)
references
References 85 publications
3
44
0
4
Order By: Relevance
“…Abnormalities were observed in neuronal precursors derived from individuals with Timothy syndrome; the expression of >200 genes were altered, many of them CREB-dependent (Pasca et al, 2011). When subjected to an unbiased systems biology analysis (Tian et al, 2014), the pattern of differences in gene expression was compatible with involvement of known Ca 2+ -dependent transcriptional regulators, including CREB, NFAT, MEF2, and FOXO. The analysis uncovered Ca 2+ -dependent co-expression modules that reflect distinct aspects of TS, including intellectual disability and ASD-related phenotypes.…”
Section: Diverse Systems For Sensor-mediated Control Of Gene Expressionmentioning
confidence: 91%
See 1 more Smart Citation
“…Abnormalities were observed in neuronal precursors derived from individuals with Timothy syndrome; the expression of >200 genes were altered, many of them CREB-dependent (Pasca et al, 2011). When subjected to an unbiased systems biology analysis (Tian et al, 2014), the pattern of differences in gene expression was compatible with involvement of known Ca 2+ -dependent transcriptional regulators, including CREB, NFAT, MEF2, and FOXO. The analysis uncovered Ca 2+ -dependent co-expression modules that reflect distinct aspects of TS, including intellectual disability and ASD-related phenotypes.…”
Section: Diverse Systems For Sensor-mediated Control Of Gene Expressionmentioning
confidence: 91%
“…In turn, this organization spurs us to offer some fresh perspective to multiple themes in ASD research. With respect to signaling from synapse to nucleus (Ebert and Greenberg, 2013), we reopen the question of how cascades of ASD-related proteins (Ma et al, 2014) may control the expression of other ASD-related genes (Tian et al, 2014). Regarding synaptic plasticity by local regulation of protein synthesis (Aguilar-Valles et al, 2015; Fernandez et al, 2013; Kelleher and Bear, 2008; Kelleher et al, 2004; Niere et al, 2012), we meld the concept of coordination amongst neighboring dendritic synapses (Bourne and Harris, 2012; Rabinowitch and Segev, 2008) with ideas about ASD as dysfunctional homeostasis (Huguet et al, 2013; Ramocki and Zoghbi, 2008; Toro et al, 2010).…”
Section: Introduction and Plan Of Presentationmentioning
confidence: 99%
“…A more recent genome-wide weighted coexpression network analysis on neural progenitors and neurons from individuals with Timothy syndrome, an autism spectrum disorder resulting from mutations in the gene encoding L-type CaV1.2 Ca 2+ channels, suggested that the disease may be caused by disturbances in transcriptional activities of Ca 2+ -dependent signaling molecules like FOX proteins, MEF2, CREB, and NFATs [247]. …”
Section: Controversial Roles In Nervous System Diseasesmentioning
confidence: 99%
“…HiPSCs derived from these patients had abnormal differentiation tendencies and differentiated neurons had reduced expression of genes marking lower cortical layers and callosal projection neurons. The same group later used a bioinformatics approach, integrating co-expression network analysis and transcription factor binding analysis, to provide mechanisms by which altered calcium signaling generates altered level of calcium-dependent transcriptional regulators leading to the transcriptional network changes observed in TS patient-derived neurons 113 . Another group reported that hiPSC-derived neurons from individuals with Timothy syndrome have activity-dependent dendrite retraction 114 .…”
Section: Induced-pluripotent Stem Cell Models Of Neurodevelopmentamentioning
confidence: 99%